ANALISA KINERJA PAD ARUAS JALAN JENDRAL A.YANI DENGAN PERTUMBUHAN LALU LINTAS - SUSILO, AGUS (KURVA S JURNAL MAHASISWA, 2012)
In this study, which is used to analyze the data is based on the existing regulations in the manual Indonesian road capacity (MKJI) 1997.The purpose of the study as follows:To know the capacity that occurred on Jendral A. Yani road.To know the level of service on Jendral A. Yani road.To know the travel speeds which is occurred on Jendral A. Yani road with traffic movement with standard MKJI 1997.To know the degree of saturation that occurs in Jendral A. Yani roads with traffic movement with standard MKJI 1997.This study was conducted in Samarinda city in Jendral A. Yani road and the material which is used for the study are survey the field and record directly into some activity Jendral A. Yani road, such as transportation and obstacles side.Documenting transportation as follows:MC  = Motorcycle, scooter, three-wheeled vehicleLV    = Passenger cars, public transportation, Pick Up, Mini bus, Mini TruckHV   = Big bus, Truck > 2 AS or moreUM  = Non-motorized vehicles, bicycles, tricycles The results were obtained, and showed that :On Jendral A. Yani road shows that the level of service to an urban street roads in traffic flow condition is not stable at the level of service D (approaching unstable flow where almost all drivers will limit the volume of services that can be related to the capacity that can be tolerated (accepted) ) by the degree of saturation, 0.84.